Changes in plastochromanol-8 and tocopherols during germination in Ethiopian mustard lines with contrasting tocopherol levels. Issue 2 (11th April 2014) - García-Navarro, Elena; Pérez-Vich, Begoña; Velasco, Leonardo
Abstract Plastochromanol-8 and tocopherols are natural antioxidants with vitamin E activity that protect seeds and plants from oxidative damage. Whereas α-tocopherol is predominant in photosynthetic tissues, γ-tocopherol is more abundant in seeds. Ethiopian mustard (Brassica carinata A. Braun) seeds contain varying levels of both tocopherol forms. The objective of this research was to study changes in plastochromanol-8 and tocopherol contents during seed germination in Ethiopian mustard lines with contrasting seed tocopherol levels, and to evaluate their influence on seed germination and seedling growth. Cotyledons and radicles of seven lines with contrasting seed tocopherol levels and a control line were sampled periodically until 120 h after sowing (HAS) under light and dark conditions, and were analysed for plastochromanol-8 and tocopherol contents. The main factors genotype, tissue, light and HAS were significant for all the traits, excepting the light effect for total tocopherol content. Most of the lines showed a gradual decrease in γ-tocopherol that was nearly completely replaced by α-tocopherol at 120 HAS. However, line BCT-4, with high γ-tocopherol content in seeds, exhibited unusually high γ-tocopherol content in cotyledons and radicles during the whole sampling period. Light treatment and initial seed tocopherol levels had no influence on germination percentage. Despite significant differences for seedling development among genotypes, no clear association between seedling development and seed tocopherols was observed. The results revealed that the unusual presence of high γ-tocopherol levels in cotyledons and radicles of line BCT-4 did not have an effect on seedling growth.